Efektifitas Pelatihan Kecerdasan Emosional Terhadap Peningkatan Kecerdasan Emosional Perawat di Rumah Sakit RoyalPrima Medan - Dessy Angraeni Siregar; Ermi Girsang; Sri Lestari Ramadhani Nasution; Crismis Novalinda Ginting (STIKes Hang Tuah Pekanbaru, 2021)
Emotional intelligence is an ability such as the ability to self-motivating, frustration surviving, adjust the mood so the stress burden does not paralyze the intelligent, and empathize. The purpose of this study was to analyze the effectiveness of emotional intelligence training toward improving the emotional intelligence of nurses at the Royal Prima Hospital Medan. This research was a quasi-experimental study with a pretest-post-test design. The population in this study were nurses and the sample was 38 respondents with 19 determinate for the experimental group and 19 for the control group. The data analysis method used descriptive statistics and inferential statistics. The results showed the mean value in the pretest = 9.84 and the post-test = 13.58 which means an increase in learning evaluation after being given training compared to before being given training. For behavior evaluation, it shows the mean value in pretest = 175.8947 and after post-test = 198.7368, significantly, there was an increase after being given emotional intelligence training compared to before being given training. The t-test results showed that the emotional intelligence of nurses after being given emotional intelligence training showed an increase or a difference (p = 0.000). Based on the results of the study, it is expected that you can conduct emotional intelligence training for all hospital employees.Â